FEATURES OF LABOUR MIGRATION IN THE EURASIAN ECONOMIC UNION - Avagyan, MIisak (Bulletin of Yerevan University G: Economics, 2019)
Along with the deepening of the processes of regional economic integration, the need to improve the system for regulating international labor migration is becoming ever more urgent. One of the reasons for the increase in international labor migration is the intensive implementation of regional economic integration processes, which are also actively developing in the Eurasian Economic Union (EAEU). The article presents the features and trends of the processes occurring in the field of labor migration of the countries members of the EAEU, as well as the motivation and structured analysis of interstate labor migration within the EAEU.